2011
DOI: 10.2139/ssrn.1954075
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Welfare Losses from Hypoxia: The Case of North Carolina Brown Shrimp

Abstract: While environmental stressors such as hypoxia (low dissolved oxygen) are perceived as a threat to the productivity of coastal ecosystems, policy makers have little information about the economic consequences for fisheries. Recent work on hypoxia develops a bioeconomic model to harness microdata and quantify the effects of hypoxia on North Carolina's brown shrimp fishery. This work finds that hypoxia is responsible for a 12.9% decrease in NC brown shrimp catches from 1999-2005 in the Neuse River Estuary and Pam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
(5 reference statements)
1
15
0
Order By: Relevance
“…The trip fixed cost parameter, c, can also reflect non-market attachment to fishing as an occupation . Positive responsiveness of fishing effort to expected revenues is consistent with the discrete choice literature on fisheries in general, the particular findings of Huang et al (2012) for North Carolina brown shrimp, and the model of spatial choices for the Gulf shrimp fleet in Ran, Keithly, and Kazmierczak (2011).…”
Section: Numerical Model and Parameterizationsupporting
confidence: 79%
See 1 more Smart Citation
“…The trip fixed cost parameter, c, can also reflect non-market attachment to fishing as an occupation . Positive responsiveness of fishing effort to expected revenues is consistent with the discrete choice literature on fisheries in general, the particular findings of Huang et al (2012) for North Carolina brown shrimp, and the model of spatial choices for the Gulf shrimp fleet in Ran, Keithly, and Kazmierczak (2011).…”
Section: Numerical Model and Parameterizationsupporting
confidence: 79%
“…There is correlation between hypoxic severity and aggregate shrimp catch in the Gulf (Zimmerman and Nance 2001), but there are no causal inference studies of the phenomenon. Economists have had some success detecting effects of hypoxia on fisheries using micro data in other settings (Massey, Newbold, and Genter 2006;Huang, Smith, and Craig 2010;Huang et al, 2012), and potential effects have been explored with empirically grounded bioeconomic simulations (Knowler, Barbier, and Strand 2001;Smith 2007). Empirical work with micro data has focused on hypoxia in estuaries along the east coast of the United States and effects on catch rates.…”
Section: In This Article We Analyze the Gulf Of Mexico Brown Shrimp mentioning
confidence: 99%
“…Within the region most affected by hypoxia, these correlations are weaker and suggest negative effects on large shrimp and positive effects on small shrimp (SI Appendix, Table S2). Because establishing a causal effect of hypoxia requires a valid counterfactual, aggregate fishery landings are insufficient because so many environmental, economic, and institutional factors influence fishery outcomes (3,10,17,18). Economic studies of other, smaller fisheries have found modest economic losses from hypoxia (17)(18)(19)(20).…”
Section: Significancementioning
confidence: 99%
“…Although the mussel industry in the Limfjord apparently benefits from eutrophication, as shown by the model simulations we presented, eutrophication and hypoxia are known to harm other fishing industries (Huang and Smith 2011), with severe economic consequences (Huang et al 2012), and it is likely that other ecosystem services will increase in the Limfjord as a consequence of nutrient reductions. A possible scenario could be that stationary finfish such as plaice and flounder, which decreased dramatically during the 1980s and early 1990s, presumably because of the negative effects of nutrient loadings (Christiansen et al 2006), would return to the estuary and would support a local fishing industry.…”
Section: Discussionmentioning
confidence: 77%